1972
DOI: 10.1042/bj1270179
|View full text |Cite
|
Sign up to set email alerts
|

The isolation of glycoproteins from bovine achilles tendon and their interaction with collagen

Abstract: Two glycoprotein fractions, A and B, were isolated from bovine achilles tendon. Glycoprotein A was prepared from a 0.2m-sodium chloride extract and glycoprotein B was isolated from a 3m-magnesium chloride extract. They were free from serum proteins. Glycoprotein A was essentially free of collagen, but glycoprotein B contained about 8% collagen. Both glycoproteins gave several bands on isoelectric focusing. This technique was also used to demonstrate that both glycoprotein fractions interacted strongly with aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1972
1972
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…1), tendons exhibit high tensile strength [4][5][6] , allowing for the efficient transmission of large loads, a result of the local cell population to adapt to changes in loading conditions 7 . Further contributing to the structure and biomechanical properties are proteoglycans and glycoproteins, which function to regulate the process of collagen fibrillogenesis and control fibril diameter throughout tendon development and homeostasis [8][9][10][11][12][13] . Studies using genetically manipulated mouse models, in which decorin has been knocked out, have investigated the role of decorin, a small leucine-rich proteoglycan important to tendon structure, and have shown that the absence of decorin results in improper collagen fibril formation and decreases mechanical properties 13 .…”
Section: Tendon Structure and Functionmentioning
confidence: 99%
“…1), tendons exhibit high tensile strength [4][5][6] , allowing for the efficient transmission of large loads, a result of the local cell population to adapt to changes in loading conditions 7 . Further contributing to the structure and biomechanical properties are proteoglycans and glycoproteins, which function to regulate the process of collagen fibrillogenesis and control fibril diameter throughout tendon development and homeostasis [8][9][10][11][12][13] . Studies using genetically manipulated mouse models, in which decorin has been knocked out, have investigated the role of decorin, a small leucine-rich proteoglycan important to tendon structure, and have shown that the absence of decorin results in improper collagen fibril formation and decreases mechanical properties 13 .…”
Section: Tendon Structure and Functionmentioning
confidence: 99%
“…The answer to the planar crimping phenomenon may lie in directionally specific interfibril interactions perhaps involving acidic structural proteins or glycoproteins (Wolff et al, 1971;Anderson & Jackson, 1972;Dixon, Hunter & Steven, 1972) or mucopolysaccharides (Bychkov, Nikolaeva & Kharlomova, 1968) or both. The collagen fibril itself might have an underlying planarity resulting from the packing of microfibrils within it; this planarity would be reflected in the planar waveform exhibited by the successive hierarchies.…”
Section: J Gathercole a Keller And? S Shahmentioning
confidence: 99%
“…Interesting, too, is the absence of sialic acid, an argument in favor of its collagen nature. The second, GP2, which contains no hydroxylysine, but glucose and sialic acids (2.5%), is probably related to a mixture of collagen structures and non collagen glycoproteins, analogous to those which A nderson and Jackson [29] recently found in the Achilles tendon of bovines.…”
Section: Od --------278 Nmmentioning
confidence: 99%